Reasons and multilevel factors associated with unscheduled contraceptive use discontinuation in Ethiopia: evidence from Ethiopian demographic and health survey 2016 - Kibrom Taame Weldemariam; Kebede Embaye Gezae; Haftom Temesgen Abebe (BMC, 2019)
Abstract Background Contraceptive discontinuations for reasons other than the desire for pregnancy are a public health concern because of their negative effect on reproductive health outcomes. In Ethiopia, the contraceptive discontinuation rate is increasing; however the factors associated are poorly understood. So this study was aimed at assessing reasons and multilevel factors for unscheduled contraceptive use discontinuation. Methods This is a cross-sectional study of Ethiopian women who participated in the Ethiopian demographic health survey from January 18, 2016, to June 27, 2016. Ever using any contraceptive with in the calendar of the survey were an inclusion criteria for which 3835 women were found eligible. The data were analyzed using multilevel binary logistic regression in STATA version 14. Variables with p-value less than 0.05 were considered as statistically significant, and reported using adjusted odds ratio and 95% confidence interval. Median odds ratio and interval odds ratio, to quantify the magnitude of the general and specific contextual effect respectively, were used. Receiver operating characteristics curve and akaike's information criterion were used for model comparison. Result The prevalence of unscheduled contraceptive use discontinuation was 46.18% for the principal reason of method related problems (Side effects-45.3%, needing better method-33.6%, and inconvenience-21.1%,). Women heading a household (AOR = 1.281, 95%CI 1.079-1.520), women who had no work (AOR = 0.812, 95%CI 0.673, 0.979) compared to professionals, living in poorest house hold income (AOR = 0.753, 95%CI 0.567, 0.997) compared to middle, residing in community with low contraceptive utilization rate (AOR = 1.945, 95%CI 1.618, 2.339), residing in poor community (AOR = 0.763, 95%CI 0.596-0.997), and having more children, and region were found to be significant predictors of unscheduled contraceptive use discontinuation. Conclusion Method related problems were found to contribute for more than half of the contraceptive use discontinuation. Both individual and community level factors were found to significantly influence the Unscheduled contraceptive use discontinuation. The outcome was common in groups who could have more social interactions and knowledge on which myths and rumors are common. So strengthening the efforts to reduce contraceptive use discontinuation and quality of contraceptive service provision could be important.